2003
DOI: 10.1210/en.2002-0185
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor II Allows Prolonged Blood Glucose Normalization with a Reduced Islet Cell Mass Transplantation

Abstract: IGF-II has been reported to decrease neonatal islet cell apoptosis and in vitro adult islet cell necrosis and apoptosis, but the usefulness of IGF-II in a transplantation setting is unknown. We evaluated the effect of in vitro IGF-II incubations on microencapsulated rat islet survival both in vitro and in minimal mass transplantations into diabetic mice. After 6 d in culture, fresh examinations, histology, fluorescence microscopy, sodium 3'-[1-(phenyl-amino-carbonyl)-3,4-tetrazolium]-bis (4-methoxy-6-nitro)-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 46 publications
2
38
0
Order By: Relevance
“…This number of islets was based on our previous experiments. 6 When non-encapsulated islets were used, only two out of five recipients became normoglycemic, and they maintained this normoglycemia only for a period of 12 and 31 days, respectively. When islets encapsulated alone were transplanted, normoglycemia was induced in 71% (5/7) of the recipients ( Figure 6).…”
Section: Effect Of Encapsulated Cells On Microcapsule Morphologymentioning
confidence: 97%
See 3 more Smart Citations
“…This number of islets was based on our previous experiments. 6 When non-encapsulated islets were used, only two out of five recipients became normoglycemic, and they maintained this normoglycemia only for a period of 12 and 31 days, respectively. When islets encapsulated alone were transplanted, normoglycemia was induced in 71% (5/7) of the recipients ( Figure 6).…”
Section: Effect Of Encapsulated Cells On Microcapsule Morphologymentioning
confidence: 97%
“…5 We have investigated the use of IGF-II in a transplantation setting. 6 In vitro studies showed that IGF-II prevents the apoptosis and necrosis of microencapsulated mouse islet cells in a dose-dependent manner. In a marginal islet mass transplantation model, pre-transplantation IGF-II incubations allowed prolonged blood glucose normalization in a higher proportion (B200%) of diabetic mice, using a reduced (50%) amount of islets.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…IGF2 has been shown to promote pancreatic b-cell survival against apoptotic stimuli in vitro and in vivo (Rabinovitch et al 1982, Swenne et al 1987, Hogg et al 1993, Ilieva et al 1999, Robitaille et al 2003, Jourdan et al 2011 and induce proliferation in a growth-arrested mouse b-cell line (Milo-Landesman & Efrat 2002). IGF2 protects pre-diabetic NOD mouse islets from the cytotoxic actions of IL1b by the mechanisms that include a reduction in apoptosis (Hill et al 1999b).…”
Section: Apoptosis In Islet Transplantation: the Role For Pro-inflammmentioning
confidence: 99%